Making a case for the continued protection of the identity of young offenders who turn 18 during criminal proceedings under South African law compared with the law of England and Wales - Skelton, Ann, 1961- (University of Pretoria, 2018)
Mini Dissertation (LLM)--University of Pretoria, 2017.